Growth Differentiation Factor 15 Predicts All-Cause Morbidity and Mortality in Stable Coronary Heart Disease. (6th January 2020) - Hagström, Emil; Held, Claes; Stewart, Ralph A H; Aylward, Philip E; Budaj, Andrzej; Cannon, Christopher P; Koenig, Wolfgang; Krug-Gourley, Sue; Mohler, Emile R; Steg, Philippe Gabriel; Tarka, Elizabeth; Östlund, Ollie; et al.
Abstract: BACKGROUND: Higher growth differentiation factor 15 (GDF-15) concentrations are associated with cardiovascular (CV) and non-CV morbidity and mortality. However, information on associations between GDF-15 and the risk of specific CV and non-CV events in stable coronary heart disease (CHD) patients is limited. METHODS: In 14 577 patients with stable CHD participating in the Stabilization of Atherosclerotic Plaque by Initiation of Darapladib Therapy Trial (STABILITY), GDF-15 and other prognostic biomarkers (N-terminal pro–B-type natriuretic peptide, high-sensitivity troponin T, cystatin C, and high-sensitivity C-reactive protein) were measured. In adjusted Cox regression models, the associations between GDF-15 and the composite CV end point [CV death, myocardial infarction (MI), and stroke], as well as other CV and non-CV events, were assessed. RESULTS: The median concentration (interquartile range) of GDF-15 at baseline was 1253 (915–1827) ng/L. The hazard ratio for the composite end point for the highest compared to the lowest quartile of GDF-15 was 1.8 (95% CI, 1.5–2.2); for CV death, 2.63 (1.9–3.6); for sudden death, 3.06 (1.9–4.8); for heart failure (HF) death, 4.3 (1.3–14); for cancer death, 2.5 (1.3–4.7); for hospitalization for HF, 5.8 (3.2–10); for MI 1.4 (95% CI, 1.1–1.9); and for stroke, 1.8 (95% CI, 1.1–2.8). After adjustment for other prognostic biomarkers, GDF-15 remained significantly associated with all outcomes except for MI. CONCLUSIONS: In stable CHD, GDF-15 was independently associated with CV, non-CV, and cancer mortality, as well as with MI and stroke. When also adjusting for other prognostic biomarkers, the associations to all fatal and nonfatal events were maintained except for MI. Information on GDF-15, therefore, might be helpful when assessing the risk of adverse outcomes in patients with stable CHD. ClinicalTrials.gov Identifier: NCT00799903